Industry profile of Korean-Owned establishments in Iloilo City - Capaque, Maricon C.; Eguia, Yoko Marie A.; Leonida, Gerlie Grace S.; Parreño, Daisy emily B.; Valasote, Karyn-Flor T.
The group visited some Korean businesses with the following objectives: 1. To determine the trend of the existing Korean businesses in Iloilo City ; 2. To identify the factors that influenced them to put up their business ; 3.To know the factors that contributes to their profitability ; To be familiar with their marketing strategies as well as the problems they encountered while running their business ; 5. To be able to recognize their contributions to the economy of Iloilo. This focused only on five different Korean business in Iloilo City namely tutorial services, restaurant, trading, internet station and grocery store. It included the 2005, 2006 and 2007 Korean owned business registered in the Department of Trade and Industry and Exchange Commission in Iloilo City. Questions were formulated fr use in interviews, and secondary data were culled from the internet, newspapers, magazines and other printed materials. Interviews were conducted with the owners and managers of the businesses as well as with employee of the selected government agencies. The results of the interviews were classified according to their business type. Based on interviews conducted by the group, Koreans set up their business primarily to cater to their financial needs and also to the physiological and educational needs of their fellow Koreans. The increasing population of Korean nationals in Iloilo City serves as a potential market for Korean businesses. Korean entrepreneurs usually obtain capital from their savings, sometimes with the aid of their Filipino partners. However, they find difficulty in owning the business themselves due to the Foreign Investment Act which provides limitation to the holding of business by foreign nationals. To remedy this, they register their businesses under the name of a Filipino colleague, or engage in partnerships. Since almost all of these businesses target the same type and group of consumers, competition is very tough. Although competition is harsh, it helps in the improvement of the products and services offered by these businesses. The prices of the products offered by Korean businessmen balance the purchasing power of their market. Since Koreans are capable of availing high-priced commodities, products of these businesses are affordable for them. Most of the firms use the same methods of advertising- through flyers, leaflets, posters, and word of mouth. They do not pay much attention in promoting their products. In terms of human resource, they employ Filipinos who, for them are industrious, reliable, and respectful. All of the owners pay their employees on time and above-minimum-wage salary. Each of these businesses contributes to the welfare of Iloilo economy through taxes they pay, and employment they provide. Some offer technologically-advanced products like cell phones and computers.